Effect of environmental factors on seasonal abundance of a coccid in Pteris biaurita L. (Pteridaceae) from Deolo hills, Kalimpong, West bengal - Biplab Patra (Journal of Research in Biology, 2011)
Insect – fern interaction is reported as a rare event of phytophagy from Eastern Himalaya. The scale is a host specific opportunistic feeder, feeds exclusively on the abaxial surface of mature pinnae of Pteris biaurita. Population density of the scale exhibited significant linear positive correlation with environmental factors (all r > .56, p< 0.05) of the study site. Rain fall, atmospheric temperature and relative humidity have positive influence over seasonal variation in scale density